HUBUNGAN KADAR HEMOGLOBIN DAN KADAR GULA DARAH TERHADAP PENDERITA DIABETES MELITUS TIPE II - Andini Kusdiantini; Anjani Asty (Jurnal Infokes, 2024)
Type 2 diabetes mellitus is a disease of hyperglycemia due to decreased insulin secretion by pancreatic beta cells or impaired insulin function. An increase in blood sugar can increase reactive oxygen species (ROS), resulting in oxidative stress. Oxidative stress causes hemolysis of red blood cells, so that in people with type 2 diabetes mellitus hemoglobin levels decrease. The aim of this research is to determine the relationship between hemoglobin levels and blood glucose levels in people with type 2 diabetes mellitus. This research was carried out using quantitative methods using correlation study techniques, which is a study to collect data obtained by measuring and recording the results of checking hemoglobin levels and blood glucose levels in type 2 diabetes mellitus sufferers at the Sumedang Regional General Hospital. The results of the research were that there was no relationship between hemoglobin levels and blood glucose levels in people with type 2 diabetes mellitus.Keywords: Diabetes mellitus type 2, Hemoglobin, Blood Glucose